2018
DOI: 10.1590/1677-5449.009517
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurisma da artéria temporal superficial: relato de três casos

Abstract: Resumo O pseudoaneurisma da artéria temporal superficial é um evento raro. Ocorre principalmente em homens jovens em decorrência de traumatismo craniano fechado. A maioria dos casos é assintomática, podendo eventualmente haver associação com sintomas vagos. A rotura do pseudoaneurisma e o desenvolvimento de déficits neurológicos são complicações esporádicas. Os autores relatam três casos de pseudoaneurisma de artéria temporal superficial pós-traumatismo craniano fechado. Os pacientes foram manejados com suces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Madhusudan et al 5 reported an extradural hematoma case after a ruptured STA pseudoaneurysm, causing extensive symptomatology, as paresis and dysphasia. Although they may range 0.5-5.7 cm in diameter, most are between 1-1.5 cm 6 . The evolution is commonly between 2 to 6 weeks after the causative traumatic incident 4 , in contrast to this reported case, which became noticeable only after 2 years.…”
Section: Introduction Case Presentation O Conhecimento Dessa Condição é Importante Para O Diagnóstico Etiológico De Uma Cefaleia Temporalmentioning
confidence: 99%
See 1 more Smart Citation
“…Madhusudan et al 5 reported an extradural hematoma case after a ruptured STA pseudoaneurysm, causing extensive symptomatology, as paresis and dysphasia. Although they may range 0.5-5.7 cm in diameter, most are between 1-1.5 cm 6 . The evolution is commonly between 2 to 6 weeks after the causative traumatic incident 4 , in contrast to this reported case, which became noticeable only after 2 years.…”
Section: Introduction Case Presentation O Conhecimento Dessa Condição é Importante Para O Diagnóstico Etiológico De Uma Cefaleia Temporalmentioning
confidence: 99%
“…The STA pseudoaneurysms usually have a benign clinical presentation and are generally secondary to TBI. Although usually presented as asymptomatic, the most common symptoms, besides the pulsatile mass on the level of the injured artery, are headache and discomfort at the lesion's location, commonly because of the involvement of nervous structures adjacent to the lesion 6 . The clinical history and the physical examination were useful to guide the diagnosis.…”
Section: Introduction Case Presentation O Conhecimento Dessa Condição é Importante Para O Diagnóstico Etiológico De Uma Cefaleia Temporalmentioning
confidence: 99%